The Role of Self-Compassion in Psychological Well-Being Among Young Adults from Single-Parent Families - Fellicia Aghata, Wisang; Handayani, Nita Sri; Konradus, Natalia (Jurnal Kesehatan dan Kedokteran, 2026)
Entering young adulthood involves major role transitions and increasing responsibilities that require effective psychological adaptation. For individuals raised in single-parent families, limited parental support and the absence of one parental figure may create additional challenges to achieving psychological well-being. In this context, self-compassion may function as an important internal resource that helps individuals cope with adversity and maintain positive psychological functioning. Objective: This study aimed to examine the role of self-compassion in promoting psychological well-being among young adults from single-parent families. Method: This study employed a quantitative approach with a cross-sectional design. Data were collected through self-report questionnaires from 130 young adults from single-parent families selected using purposive sampling. The data were analyzed using simple linear regression to assess the contribution of self-compassion to psychological well-being. Findings: The results showed that self-compassion had a significant role in predicting psychological well-being (p < 0.05). The coefficient of determination (R²) was 0.481, indicating that self-compassion explained 48.1% of the variance in psychological well-being. In addition, both self-compassion and psychological well-being were found to be at moderate levels among participants. Implications: These findings suggest that strengthening self-compassion may serve as an effective psychological resource to support the well-being of young adults from single-parent families. The results also provide practical implications for counselors, psychologists, and family-based support programs in developing interventions that enhance adaptive coping and emotional resilience. Originality: The originality of this study lies in its focus on young adults raised by a single parent due to parental loss, highlighting self-compassion as a protective factor within this specific population. This study contributes empirical evidence to the growing body of literature on positive psychological resources in vulnerable family contexts.